Student Resistance to Dictatorship in Chile, 1973-1990 - Smith, Richard G. author. (orcid)0000-0001-5894-4600 Link aut Link
XXVI, 346 p. 17 illus., 6 illus. in color.
Keywords: This book documents and analyses Chilean university and school students’ opposition to the Pinochet regime during the latter years of the 1970s and the 1980s. The book focuses on key episodes such as the establishment of cultural groups within the militarily controlled universities that enabled students to congregate and exchange ideas for the first time since the 1973 coup; how university and secondary school students created their own democratic institutions to challenge the regime-appointed bodies; and how these eventually led to the restoration of the national federations that had been banned by the military government. The author explores the key relationship between the vertically organised, underground political parties, and the horizontally organised, broad, non-partisan organisations created by the students, arguing that this structure brought advantages to the movement. The students’ contribution to the national protests in the 1980s ensured that opposition to the regime was highly visible in the city centre, resulting in a socially broadened opposition with a focus on youth, rather than disenfranchisement and poverty. Offering a detailed account of different forms of student activism, this book evaluates the role of school and university students within the broader anti-dictatorship opposition in Chile. Richard G. Smith originally trained as a chemist before a career in consumer product innovation took him all over the world, including three years living in Buenos Aires and many more working and travelling across the length and breadth of Latin America. He was Visiting Fellow at the University of London’s Centre for Latin American and Caribbean Studies (2022-23), and is an Honorary Research Fellow in the University of Liverpool’s Department of History, where he previously studied. During his time at Liverpool, Richard taught Contemporary Latin American Politics as a Graduate Teaching Assistant, and was Visiting International Fellow at the University of Georgia, USA, which included research, lecturing and teaching.